Service quality of Singapore tour operators : Chinese tourists' perspectives. - Choo, Wen Min. (2008)
To investigate the overall service quality of Singapore tour operators by analysing the expectations and perceptions of Chinese tourists. To identify Singapore tour operators weaknesses from Chinese tourists' perspectives, such that financial resources can be better directed to these areas. This would distinguish Singapore from the other destinations and thus attracts more Chinese tourists to come Singapore for holiday.